Transformasi Pembelajaran IPS dengan Pendekatan Merdeka Belajar di Era Digital - Mansyur, Alif Ilman; Nana Supriatna (Journal Education Innovation (JEI), 2024)
Merdeka Belajar policy in Indonesia encourages teachers to be more creative and innovative in teaching practices. This research aims to explore the implementation of Merdeka Belajar policy in the context of Social Science education in the digital space. This research uses a qualitative approach, which involves interviews with teachers and observations of their teaching practices. The research findings reveal that teachers have adopted various strategies to implement Merdeka Belajar policy in their social studies lessons, such as using online platforms, incorporating multimedia resources, and implementing project-based learning. However, this study also identified several challenges faced by teachers, such as lack of access to technology and the need for professional development. This research concludes that the implementation of Merdeka Belajar policy has the potential to improve the quality of social studies education in Indonesia. However, it is important to address the challenges teachers face in order to ensure the success of policy implementation